San Marco in Le Corbusier, San Marco in Bogota - O’byrne, María Cecilia (Journal of Architecture and Urbanism, 2016)
There are many ties between the monumental compound of San Marco in Venice and Le Corbusier. This article follows, studies and organizes these ties to link them to how he resolves the urban project for the Administrative Centre for Bogotá. In it, Le Corbusier leaves aside the isolated buildings that characterize his way of solving urban space, to use the chaos, the turmoil in the compound and uniformity in the detail, which are the features of San Marco: “An ideal and precise conclusion [that] under the rule of Louis XIV had been alrfeady formulated by Abbé Laugier”, says Le Corbusier in Urbanisme.